Two-Level Air Compressor Maintenance Optimization On SV Vessels of STELLA 28 - Waris Wibowo; Ningrum Astriawati; Prasetya Sigit Santosa; Yusmario Setiadi (Nama Jurnal Akmi, 2023)
A compressor is one component of the working air system on board the ship which is related to carrying out smooth ship motion. Auxiliary aircraft two-level air compressors in operation on board ships for the start process of the main engine, generator, and bow thruster which are important parts in the ship, and also for the process of processing ship motion with ships using a pneumatic system gearbox. The purpose of this study was to optimize the maintenance of two-level air compressors on SV Ships. Stella 28. This research is a research with qualitative descriptive analysis. Data collection techniques are obtained through field research by combining observation, documentation, interview, and literature study methods. The result of this study is the optimization of maintenance and two-level air compressors on SV ships. Stella 28 at PT. Sowohi Kentiti JayA is good. Treatments carried out in SV. Stella 28 includes routine replacement of compressor LO according to the manual book, sediment water flushing in the air pipe and also on wind bottles, and checking the manometer and thermometer that have been done properly.